Activated 5′flanking region of NANOGP8 in a self‐renewal environment is associated with increased sphere formation and tumor growth of prostate cancer cells. Issue 4 (7th December 2013) - Zhang, Kai; Fowler, Marcie; Glass, Jonathan; Yin, Hong
Abstract INTRODUCTION NANOGP8 is a retrogene which encodes a full‐length protein similar to the NANOG1 gene. The expression of NANOGP8 has been documented in several cancers and is related to cell proliferation and tumor development. However, the regulation of NANOGP8 expression has not been investigated. Therefore, the role of NANOGP8 in cell proliferation has not been completely understood. METHODS We evaluate the expression of NANOG1 and NANOGP8 in prostate cancer cell lines and primary cultures of prostate tissues. We investigate clonogenicity, sphere formation, and xenograft tumor growth of prostate cancer cells with an activated 5′flanking region of NANOGP8. We examine the role of NANOGP8 in cell cycle progression. RESULTS In the prostate cells the NANOG RNA was transcribed from NANOGP8 and not from NANOG1. Cells with the activated 5′flanking region of NANOGP8 exhibited enhanced clonogenicity, sphere formation, and xenograft tumor growth. The sphere culture and tumor initiation mouse mode promoted the activation of the 5′flanking region of NANOGP8. Forced expression of NANOGP8 increased the entry into the cell cycle. DISCUSSION In prostate cells NANOGP8 is a predominant molecule of NANOG. The activation of 5′flanking sequence of NANOGP8 could play a role in the regulation of the stem‐like properties of cancer stem cells and prostate tumor initiation and development. The microenvironment favoring cancer stem cells could promote the activation of the 5′flanking region of NANOGP8. Prostate 74:381–394, 2014. © 2013 Wiley Periodicals, Inc.